Left atrial appendage emptying velocity and left ventricular function as predictors of inotropic support in patients undergoing elective off-pump coronary artery bypass grafting - Varun Arora; Srikanth Gujja; Rajesh Thosani; Kamal Sharma; Himani Pandya (The Indian Anaesthetists' Forum)
Background: Patients undergoing elective off-pump coronary artery bypass grafting (CABG) are at risk of hemodynamic instability, ischemia, arrhythmia, and dysfunction. These events need to be managed by pharmacological supports or relieving of mechanical obstruction (octopus) of the heart to maintain the hemodynamic stability. There is a paucity of data on the effect of left ventricular (LV) dysfunction on left atrial appendage (LAA) emptying velocity. We evaluated the relationship between LV function and LAA emptying velocity and requirement of inotropic support perioperatively. Materials and Methods: In this prospective open-label all-comer study, fifty patients undergoing elective off-pump CABG under general anesthesia, we measured LAA emptying velocity by pulsed wave Doppler and evaluated if it could predict the need for inotropes perioperatively. It is a case series of 50 patients without a comparator arm. We measured pulsed wave Doppler across the mitral valve leaflet and early mitral inflow velocity (Evel) and late mitral inflow velocity, tissue Doppler at the lateral annulus of the mitral valve (e’) and also calculated the ratio of Evel and e’. Need for inotrope in the intraoperative and postoperative period was captured perioperatively. Vasoactive-inotropic score (VIS) was calculated for all the patients. Results: The VIS was significant (P < 0.0001, with odds ratio of 131.6 and confidence interval of 95% (0.9–1). However, there was no significant correlation between ejection fraction (EF) and VIS (P = 0.87). In patients with the need of inotropes, LAA emptying velocity was significantly increased in the postgrafting period as compared to the pregrafting period (75.64 cm/s vs. 57.9 cm/s, P < 0.001). Conclusion: The assessment of LAA emptying velocity value was a useful predictor of the need of inotropic support during off-pump surgery, especially during Obtuse marginal and Ramus grafting. This study paves the need of larger case–control studies to validate the findings.